Characterization of two Arabidopsis thaliana myb-like proteins showing affinity to telomeric DNA sequence - Schrumpfová, Petra; Kuchar, Milan; Miková, Gabriela; Skrísovská, Lenka; Kubicárová, Tatiana; Fajkus, Jirí (Genome, 2004)
Telomere-binding proteins participate in forming a functional nucleoprotein structure at chromosome ends. Using a genomic approach, two Arabidopsis thaliana genes coding for candidate Myb-like telomere binding proteins were cloned and expressed in E. coli. Both proteins, termed AtTBP2 (accession Nos. T46051 (protein database) and GI:638639 (nucleotide database); 295 amino acids, 32 kDa, pI 9.53) and AtTBP3 (BAB08466, GI:9757879; 299 amino acids, 33 kDa, pI 9.88), contain a single Myb-like DNA-binding domain at the N-terminus, and a histone H1/H5-like DNA-binding domain in the middle of the protein sequence. Both proteins are expressed in various A. thaliana tissues. Using the two-hybrid system interaction between the proteins AtTBP2 and AtTBP3 and self interactions of each of the proteins were detected. Gel-retardation assays revealed that each of the two proteins is able to bind the G-rich strand and double-stranded DNA of plant telomeric sequence with an affinity proportional to a number of telomeric repeats. Substrates bearing a non-telomeric DNA sequence positioned between two telomeric repeats were bound with an efficiency depending on the length of interrupting sequence. The ability to bind variant telomere sequences decreased with sequence divergence from the A. thaliana telomeric DNA. None of the proteins alone or their mixture affects telomerase activity in vitro. Correspondingly, no interaction was observed between any of two proteins and the Arabidopsis telomerase reverse transcriptase catalytic subunit TERT (accession No. AF172097) using two-hybrid assay.
Keywords: protoonkogenní proteiny c-myb; proteiny huseníčku; exprese genu; Telomere-Binding Proteins; sekvence nukleotidů; telomerasa; Gene Expression; telomery; Molecular Sequence Data; Protein Binding; klonování DNA; Electrophoretic Mobility Shift Assay; molekulární sekvence - údaje; mapování interakce mezi proteiny; Telomerase; Arabidopsis Proteins; Protein Interaction Mapping; retardační test; Arabidopsis; proteiny vázající telomery; Proto-Oncogene Proteins c-myb; Telomere; Base Sequence; Two-Hybrid System Techniques; rostlinné proteiny; kompetitivní vazba; vazba proteinů; Binding, Competitive; Plant Proteins; techniky dvojhybridového systému; Cloning, Molecular; terciární struktura proteinů; Protein Structure, Tertiary